STRATEGIC MANAGEMENT AT SEVERAL OF THE BEST UNIVERSITIES IN INDONESIA - Rizal Ramdan Padmakusumah; R. Wedi Rusmawan Kusumah; Solahuddin Ismail (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
The strategic management process of each category of organization will undoubtedly be distinctive. This study aims to ascertain the strategic management process in higher education institutions in Indonesia. This research is a qualitative case study that examines the University of Indonesia (UI), Gajah Mada University (UGM), Bogor Agricultural Institute (IPB), Telkom University (TELU), Indonesian Islamic University (UII), and Muhammadiyah University of Surakarta (UMS). The strategic management process at Indonesian HEI is described or concluded by analyzing secondary data in the form of strategic plan documents compiled with analysis of primary data in the form of interviews with experts in the field of higher education. The research findings indicate that the strategic management process in Indonesian higher education institutions is comprised of four stages: (1) environmental analysis, (2) strategy formulation, (3) strategy implementation, and (4) evaluation control. An example of the originality or uniqueness of the strategic management process in Indonesian higher education institutions is internal environmental analysis, which employs its criteria rather than the commonly used value chain analysis or functional analysis approach criteria.